Analysis of Digital Comic Media Needs Containing Local Wisdom to Improve Science Learning Outcomes in Elementary Schools - Nurvitasari, Septiana; Suryandari, Kartika Christy; Supianto, Supianto (Jurnal Mamangan, 2023)
Low science learning outcomes can hinder students' ability to understand and apply science concepts in everyday life. It is hoped that learning media that integrates local wisdom, especially through digital comic media, can increase students' interest and understanding of science. This study has three main objectives: (1) to describe the implementation of media containing local wisdom in improving students' understanding of science concepts, (2) to identify obstacles and supporting factors in the application of local wisdom-based media in the classroom, and (3) to provide strategic recommendations for teachers in developing learning media. Which relevant with context local research. This use method qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation in several classes in elementary schools. Data analysis techniques Using the interactive model from Miles and Huberman that is reduction data, presentation data, And withdrawal conclusion. Results study shows that there is no digital-based learning media, still relying on textbooks. Not yet linked to local cultural wisdom, student outcomes are still low. The presence of digital comic media containing local wisdom as an effort to improve science learning outcomes